2013
DOI: 10.2967/jnumed.112.114066
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Imaging of the Glucagonlike Peptide 1 Receptor in the Pancreas with 68Ga-Labeled DO3A-Exendin-4

Abstract: The glucagonlike peptide 1 receptor (GLP-1R) is mainly expressed on b-cells in the islets of Langerhans and is therefore an attractive target for imaging of the b-cell mass. In the present study, 68 Ga-labeled exendin-4 was evaluated for PET imaging and quantification of GLP-1R in the pancreas. Methods: Dose escalation studies of 68 Ga-labeled 1,4,7-tris(carboxymethylaza)cyclododecane-10-azaacetyl (DO3A)-exendin-4 were performed in rats (organ distribution) and cynomolgus monkeys (PET/CT imaging) to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
102
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(104 citation statements)
references
References 13 publications
1
102
1
Order By: Relevance
“…[ The ability to repeatedly quantify the amount of remaining b-cells by noninvasive methods would be of significant importance to obtain further insights into the pathophysiology of diabetes, as well as a tool to evaluate new therapies aiming to prevent b-cell loss. Significant efforts have been made in order to develop such a method (1)(2)(3)(4)(5), but so far no clinically validated technique has been described. Despite originating from different germinal layers, pancreatic islet cells share many common developmental features with neurons, especially serotonin-producing neurons in the hindbrain (6,7).…”
mentioning
confidence: 99%
“…[ The ability to repeatedly quantify the amount of remaining b-cells by noninvasive methods would be of significant importance to obtain further insights into the pathophysiology of diabetes, as well as a tool to evaluate new therapies aiming to prevent b-cell loss. Significant efforts have been made in order to develop such a method (1)(2)(3)(4)(5), but so far no clinically validated technique has been described. Despite originating from different germinal layers, pancreatic islet cells share many common developmental features with neurons, especially serotonin-producing neurons in the hindbrain (6,7).…”
mentioning
confidence: 99%
“…The A s achieved for the individual exendin-4 radiotracers described herein are in the range of those described in the literature (13-700 GBq/mmol) for preclinical (2,7,8,11,28) and clinical investigations (9,18,19,29).…”
Section: Glp-1 Receptor Imaging In Nuclear Medicine • Bauman Et Almentioning
confidence: 56%
“…These derivatives were functionalized with different chelators (diethylenetriaminepentaacetic acid [DTPA], hydrazinonicotinic acid, DOTA, and 1,4,7-triazacyclononane,1-glutaric acid-4,7-acetic acid) suitable for radiolabeling with 111 In (2,7,8), 99m Tc (8,9), 68 Ga (7,8,(10)(11)(12), and 64 Cu (10,12,13), respectively. More recently, examples of 18 F-labeled exendins have also been described (14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Recent studies have shown that radiolabeled somatostatin receptor antagonists are preferable to agonists for in vivo peptide receptor targeting, and there are several ongoing studies across various NETs. Glucagon-like peptide-1 receptor imaging using 68 Ga-exendin-4 PET/CT (15) and 18 F-radiolabeled analogs of exendin-4 PET/CT has emerged and is highly sensitive for detecting benign insulinomas that might be missed by other imaging studies (16). Studies have also shown a high expression of C-X-C chemokine receptor type 4 in normal adrenal cortex and adrenocortical tumors, opening new avenues for imaging these tumors with peptides targeting C-X-C chemokine receptor type 4 ( 68 Ga-pentixafor) and theranostic approaches (17,18).…”
mentioning
confidence: 99%